Postpartum retained products of conception: Retrospective analysis of the association with third stage of labor placental complications. (March 2019) - Smorgick, Noam; Ayashi, Nagham; Levinsohn-Tavor, Orna; Wiener, Yifat; Betser, Moshe; Maymon, Ron
Abstract: Objective: To compare the prevalence of postpartum retained products of conception (RPOC) among parturients with a history of third stage of labor placental complications and parturients without those complications. Study design: All women operated for postpartum RPOC following vaginal delivery by hysteroscopy or suction curettage between January 2013 and December 2017 were included in the study. Their medical records were reviewed for the occurrence of third stage of labor placental complications (including early postpartum hemorrhage treated with uterotonics, manual separation of the placenta, and revision of the uterine cavity for removal of cotyledons). Results: The study cohort included 172 women operated for postpartum RPOC following vaginal delivery by operative hysteroscopy (143 cases, 83.1%) or by suction curettage (29 cases, 16.9%). Third stage of labor placental complications were reported in 65 (37.8%) cases, while 107 (62.2%) women had an uncomplicated third stage of labor. When considering all vaginal deliveries in our institution during the study period, the risk for RPOC was significantly higher among parturients with third stage of labor placental complications compared to those with an uneventful third stage of labor (3.7% versus 0.3%, p < 0.001, Odds ratio = 12.5, 95% confidence interval 9.0–17.3). Conclusion: Postpartum RPOC following vaginal delivery were more common in parturients with third stage of labor placental complications. However, the majority of postpartum RPOC cases were diagnosed in women reported to have an uncomplicated third stage of labor. Thus, focused postpartum ultrasound follow-up of women considered at risk for RPOC will not identify all cases.